PENGARUH KOMPETENSI APARATUR, PARTISIPASI MASYARAKAT, PEMANFAATAN TEKNOLOGI INFORMASI, KOMITMEN ORGANISASI, TRANSPARANSI DAN SISTEM PENGENDALIAN INTERNAL TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA (Studi pada Desa Perkebunan Afdeling 1, Desa Kampung Baru, Desa Janji Kecamatan Bilah Barat Kabupaten Labuhanbatu) - Arthur Simanjuntak; Farida Sagala; Selvina Dwi Putri (Sekolah Tinggi Ilmu Ekonomi-LMII Medan, 2023)
This research was conducted in Afdeling 1 Plantation Village, Kampung Baru Village, Promise Village, which is located in West Bilah District, Labuhanbatu Regency, North Sumatra. The population and sample in this study were 44 people, each of which was 11 officers from Afdeling 1 Village, 14 people from Kampung Baru Village, and 19 people from Janji Village. This study uses primary data obtained by using a questionnaire. While the data analysis method used in this study is the multiple linear regression analysis method which was carried out with the help of SPSS 25 software. The results in this study found that the competence of the apparatus and internal control had a significant positive effect on the accountability of village fund management. Meanwhile, community participation, the use of information technology and the commitment of village government organizations and transparency did not have a significant influence on the accountability of village fund management.